2017
DOI: 10.1073/pnas.1619588114
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 inhibits the ER stress gene regulatory network and modulates metabolic stress response

Abstract: The endoplasmic reticulum (ER) is classically linked to metabolic homeostasis via the activation of unfolded protein response (UPR), which is instructed by multiple transcriptional regulatory cascades. BRCA1 associated protein 1 (BAP1) is a tumor suppressor with deubiquitinating enzyme activity and has been implicated in chromatin regulation of gene expression. Here we show that BAP1 inhibits cell death induced by unresolved metabolic stress. This prosurvival role of BAP1 depends on its de-ubiquitinating activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 36 publications
3
62
0
Order By: Relevance
“…SLC7A11 shRNAs and SLC7A11 cDNA-containing expression vectors were described in our previous publications [18,19]. Human BAP1 cDNAs (WT and mutant) were generated as described in the our previous publication [20]. The primer sequences used in this study are listed in Table S1.…”
Section: Constructs and Reagentsmentioning
confidence: 99%
“…SLC7A11 shRNAs and SLC7A11 cDNA-containing expression vectors were described in our previous publications [18,19]. Human BAP1 cDNAs (WT and mutant) were generated as described in the our previous publication [20]. The primer sequences used in this study are listed in Table S1.…”
Section: Constructs and Reagentsmentioning
confidence: 99%
“…The BAP1 protein was recently demonstrated to play an important role in inhibiting apoptosis caused by metabolic stress such as glucose deprivation (48). The unfolded protein response (UPR) protects cells from stress caused by misfolded proteins in the endoplasmic reticulum (i.e., glucose deprivation), and if the stress is unresolved, this leads to induction of apoptosis by depleting ATP and generating reactive oxygen species (ROS).…”
Section: Bap1 Gene Protein Structure and Functionmentioning
confidence: 99%
“…The unfolded protein response (UPR) protects cells from stress caused by misfolded proteins in the endoplasmic reticulum (i.e., glucose deprivation), and if the stress is unresolved, this leads to induction of apoptosis by depleting ATP and generating reactive oxygen species (ROS). The investigators demonstrated that under metabolic stress, BAP1 complexes with PRC1 to promote the expression of genes essential for UPR by directly binding to the genes' promoters (48). Studies performed with several BAP1-null lung and renal cancer cell lines showed increased apoptotic induction following glucose deprivation, suggesting that the increased survival reported in patients with BAP1-negative MM may be due to the inability of these cancer cells to actively proliferate due to the stress caused by the high demand for glucose (48).…”
Section: Bap1 Gene Protein Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…To cope with stress, the unfolded protein response (UPR) is activated, which induces a cytoprotective effect and helps to reestablish homeostasis (Yang et al, ). The UPR has three major branches: the activating transcription factor (ATF) 6 pathway, the inositol‐requiring enzyme 1α (IRE1) pathway, and the protein kinase (PKR)‐like ER kinase (PERK) pathways (Dai et al, ). To date, many studies have confirmed that ER stress involves in several physiological and pathological process, including autophagy, inflammation, metabolic diseases, and female reproduction (Cubillos‐Ruiz, Mohamed, & Rodriguez, ; Lenzen, ; Liu, Ke, & Luo, ; Yang, Pei, Jin, Wang, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%